Disavowing Constantine: Mission, church and the social order in the theologies of John Howard Yoder and Jürgen Moltmann - Wright, Nigel Goring; (1949-...) (U.K., 2000)
This book is a timely restatement of a radical theology of church and state in the Anabaptist and Baptist traditions. Dr. Wright constructs his argument in dialogue and debate with Yoder and Moltmann, major contributors to a free church perspective.
Keywords: Yoder, John Howard -- Bibliography